2019
DOI: 10.1088/2053-1591/ab408c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of tribological properties of laser textured tungsten doped diamond like carbon coating under dry sliding conditions at various loads

Abstract: Laser micro texturing technique has shown its potential in reducing friction and wear at various mechanical interfaces such as automotive and cutting tools etc. Automotive parts are coated with Diamond-like Carbon (DLC) coatings to enhance their performance. Due to stringent condition at the automotive contacts and demand for performance enhancement, increase in performance of DLC coatings is required. In this study laser micro texturing is being combined with tungsten doped DLC coating. In order to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In contrast, the textured DLC films exhibited narrower and shallower wear tracks [232]. As previously hypothesized by Arslan et al for DLC films [205], the authors suggested that wear debris in the contact could induce graphitization [232]. GLC has also been deposited onto hard textured Si substrates, resulting in more stable friction and lower wear than smooth GLC [233].…”
Section: Indirect Structuring Of Dlcmentioning
confidence: 61%
See 3 more Smart Citations
“…In contrast, the textured DLC films exhibited narrower and shallower wear tracks [232]. As previously hypothesized by Arslan et al for DLC films [205], the authors suggested that wear debris in the contact could induce graphitization [232]. GLC has also been deposited onto hard textured Si substrates, resulting in more stable friction and lower wear than smooth GLC [233].…”
Section: Indirect Structuring Of Dlcmentioning
confidence: 61%
“…For textured DLC, the textures remove the wear debris from the contact, reducing graphitization. The difference between these two studies may lie in the texture depth, which was substantially larger in He's work (25 µm) [198] than in Arslan's work (6-8 µm), resulting in more intense stress concentrations [205]. Further, W-DLC is harder than undoped DLC, and the film was deposited onto a substantially harder substrate (hardened steel compared to a titanium alloy) in Arslan's work [205].…”
Section: Indirect Structuring Of Dlcmentioning
confidence: 95%
See 2 more Smart Citations
“…NMR spectroscopy technique is used to determine the hardness as well as elastic modulus of DLC coating [96,103]. Scratch testing technique is used to find the adhesion of DLC coating, Feld emission scanning electron microscopy (FESEM), x-ray diffraction and scanning electron microscopy (SEM) are post process techniques and used to find the wear profile and wear scar diameter [7,26,96,97,104,[107][108][109]. Raman spectroscopy is used to determine the structural properties after tribotesting.…”
Section: Characteristics Of Dlc Coatingsmentioning
confidence: 99%